Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

3-Monothiopomalidomide, a new immunomodulatory imide drug (IMiD), blunts inflammation and mitigates ischemic stroke in the rat - Kai-Yun Chen; Shih-Chang Hsueh; Pathik Parekh; Buyandelger Batsaikhan; David Tweedie; Weiming Luo; Chirag Patel; Yung-Hsiao Chiang; Nicholas Bambakidis; Barry J. Hoffer; Chi-Zong Huang; Seong-Jin Yu; et al. (GeroScience, 2025)
An overactive neuroinflammatory response is often evident in the elderly and is a significant contributor to brain tissue damage following acute ischemic stroke. Such an inflammatory response is largely mediated by microglial cells and peripheral blood mononuclear cells (PBMCs). Classical anti-inflammatory agents have not proved clinically effective in mitigating the impact of ischemic stroke but have highlighted targets for new drug development, in particular excessive proinflammatory cytokine release. The immunomodulatory imide drug (IMiD) class has shown potential in reducing neuroinflammation and switching microglial phenotypic expression away from a proinflammatory to a regenerative anti-inflammatory one. 3-Monothiopomalidomide (3-MP), a new IMiD, has a brain/plasma concentration ratio of 0.5 to 0.6, an oral bioavailability of 38.5%, and a monophasic disappearance of half-life 3.2 h following oral administration. 3-MP pretreatment mitigates lipopolysaccharide (LPS)-induced inflammation in cellular human PBMCs and, in rat studies, 3-MP pretreatment lowers proinflammatory cytokine levels in the conditioned media and in plasma and the brain, respectively. Administered systemically to rats challenged with middle cerebral artery occlusion (MCAo) and reperfusion, 3-MP post-MCAo treatment reduced infarction volume; improved body asymmetry, a behavioral measure of stroke impact; and lowered inflammation. In summary, 3-MP exerted neuroprotective effects via anti-inflammatory actions against MCAo-induced ischemic injury and represents a therapeutic that warrants further investigation as a treatment for brain damage and related disorders associated with excessive inflammation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Gastroretentive Delivery Approach to Address pH-Dependent Degradation of (+)- and (-)-Phenserine - Pratishtha Verma; Leyla Rezaei; Ramprakash Govindarajan; Nigel H. Greig; Maureen D. Donovan (AAPS PharmSciTech, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

DPP-4 inhibitors sitagliptin and PF-00734,200 mitigate dopaminergic neurodegeneration, neuroinflammation and behavioral impairment in the rat 6-OHDA model of Parkinson’s disease - Seong-Jin Yu; Yun Wang; Hui Shen; Eun-Kyung Bae; Yazhou Li; Kumar Sambamurti; Michael A. Tones; Margaret M. Zaleska; Barry J. Hoffer; Nigel H. Greig (GeroScience, 2024)
Epidemiological studies report an elevated risk of Parkinson's disease (PD) in patients with type 2 diabetes mellitus (T2DM) that is mitigated in those prescribed dipeptidyl peptidase 4 (DPP-4) inhibitors. With an objective to characterize clinically translatable doses of DPP-4 inhibitors (gliptins) in a well-characterized PD rodent model, sitagliptin, PF-00734,200 or vehicle were orally administered to rats initiated either 7-days before or 7-days after unilateral medial forebrain bundle 6-hydroxydopamine (6-OHDA) lesioning. Measures of dopaminergic cell viability, dopamine content, neuroinflammation and neurogenesis were evaluated thereafter in ipsi- and contralateral brain. Plasma and brain incretin and DPP-4 activity levels were quantified. Furthermore, brain incretin receptor levels were age-dependently evaluated in rodents, in 6-OHDA challenged animals and human subjects with/without PD. Cellular studies evaluated neurotrophic/neuroprotective actions of combined incretin administration. Pre-treatment with oral sitagliptin or PF-00734,200 reduced methamphetamine (meth)-induced rotation post-lesioning and dopaminergic degeneration in lesioned substantia nigra pars compacta (SNc) and striatum. Direct intracerebroventricular gliptin administration lacked neuroprotective actions, indicating that systemic incretin-mediated mechanisms underpin gliptin-induced favorable brain effects. Post-treatment with a threefold higher oral gliptin dose, likewise, mitigated meth-induced rotation, dopaminergic neurodegeneration and neuroinflammation, and augmented neurogenesis. These gliptin-induced actions associated with 70–80% plasma and 20–30% brain DPP-4 inhibition, and elevated plasma and brain incretin levels. Brain incretin receptor protein levels were age-dependently maintained in rodents, preserved in rats challenged with 6-OHDA, and in humans with PD. Combined GLP-1 and GIP receptor activation in neuronal cultures resulted in neurotrophic/neuroprotective actions superior to single agonists alone. In conclusion, these studies support further evaluation of the repurposing of clinically approved gliptins as a treatment strategy for PD.

Sitagliptin elevates plasma and CSF incretin levels following oral administration to nonhuman primates: relevance for neurodegenerative disorders - Yazhou Li; Kelli L. Vaughan; Yun Wang; Seong-Jin Yu; Eun-Kyung Bae; Ian A. Tamargo; Katherine O. Kopp; David Tweedie; Cheng-Chuan Chiang; Keith T. Schmidt; Debomoy K. Lahiri; Michael A. Tones; et al. (GeroScience, 2024)
The endogenous incretins glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) possess neurotrophic, neuroprotective, and anti-neuroinflammatory actions. The dipeptidyl peptidase 4 (DPP-4) inhibitor sitagliptin reduces degradation of endogenous GLP-1 and GIP, and, thereby, extends the circulation of these protective peptides. The current nonhuman primate (NHP) study evaluates whether human translational sitagliptin doses can elevate systemic and central nervous system (CNS) levels of GLP-1/GIP in naive, non-lesioned NHPs, in line with our prior rodent studies that demonstrated sitagliptin efficacy in preclinical models of Parkinson’s disease (PD). PD is an age-associated neurodegenerative disorder whose current treatment is inadequate. Repositioning of the well-tolerated and efficacious diabetes drug sitagliptin provides a rapid approach to add to the therapeutic armamentarium for PD. The pharmacokinetics and pharmacodynamics of 3 oral sitagliptin doses (5, 20, and 100 mg/kg), equivalent to the routine clinical dose, a tolerated higher clinical dose and a maximal dose in monkey, were evaluated. Peak plasma sitagliptin levels were aligned both with prior reports in humans administered equivalent doses and with those in rodents demonstrating reduction of PD associated neurodegeneration. Although CNS uptake of sitagliptin was low (cerebrospinal fluid (CSF)/plasma ratio 0.01), both plasma and CSF concentrations of GLP-1/GIP were elevated in line with efficacy in prior rodent PD studies. Additional cellular studies evaluating human SH-SY5Y and primary rat ventral mesencephalic cultures challenged with 6-hydroxydopamine, established cellular models of PD, demonstrated that joint treatment with GLP-1 + GIP mitigated cell death, particularly when combined with DPP-4 inhibition to maintain incretin levels. In conclusion, this study provides a supportive translational step towards the clinical evaluation of sitagliptin in PD and other neurodegenerative disorders for which aging, similarly, is the greatest risk factor.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Pifithrin-Alpha Reduces Methamphetamine Neurotoxicity in Cultured Dopaminergic Neurons - Yun-Hsiang Chen; Eunkyung Bae; Hsi Chen; Seong-Jin Yu; Brandon K Harvey; Nigel H Greig; Yun Wang (Neurotoxicity Research, 2019)

Role of viruses, prions and miRNA in neurodegenerative disorders and dementia - Sayed Sartaj Sohrab; Mohd Suhail; Ashraf Ali; Mohammad Amjad Kamal; Azamal Husen; Fahim Ahmad; Esam Ibraheem Azhar; Nigel H. Greig (VirusDisease, 2018)

Dopaminergic Neuron-Specific Deletion of p53 Gene Attenuates Methamphetamine Neurotoxicity - Tao Lu; Paul P. Kim; Nigel H. Greig; Yu Luo (Neurotoxicity Research, 2017)

Early-life events may trigger biochemical pathways for Alzheimer’s disease: the “LEARn” model - Debomoy K. Lahiri; Nasser H. Zawia; Nigel H. Greig; Kumar Sambamurti; Bryan Maloney (Biogerontology, 2008)

Soluble Neuroprotective Antioxidant Uric Acid Analogs Ameliorate Ischemic Brain Injury in Mice - Frank Haberman; Sung-Chun Tang; Thiruma V. Arumugam; Dong-Hoon Hyun; Qian-Sheng Yu; Roy G. Cutler; Zhihong Guo; Harold W. Holloway; Nigel H. Greig; Mark P. Mattson (NeuroMolecular Medicine, 2007)

Differential effects of two hexahydropyrroloindole carbamate-based anticholinesterase drugs on the amyloid beta protein pathway involved in alzheimer disease - Debomoy K. Lahiri; George M. Alley; David Tweedie; Demao Chen; Nigel H. Greig (NeuroMolecular Medicine, 2007)

Differential effects of two hexahydropyrroloindole carbamate-based anticholinesterase drugs on the amyloid beta protein pathway involved in alzheimer disease - Debomoy K. Lahiri; George M. Alley; David Tweedie; Demao Chen; Nigel H. Greig (NeuroMolecular Medicine, 2007)

Alzheimer’s disease drug discovery targeted to the APP mRNA 5′Untranslated region - Jack T. Rogers; Jeffrey D. Randall; Paul S. Eder; Xudong Huang; Ashley I. Bush; Rudolph E. Tanzi; Amanda Venti; Sandra M. Payton; Tony Giordano; Seiichi Nagano; Catherine M. Cahill; Robert Moir; et al. (Journal of Molecular Neuroscience, 2002)